Synthesis of novel series of 7, 7′-(substituted methylene)bis-imidazo[1, 2-b]pyrazoles via an acid catalyzed one-pot three-component reaction. (15th March 2018) - Driowya, Mohsine; Allouchi, Hassan; Gally, José Manuel; Bonnet, Pascal; Guillaumet, Gérald
Abstract : An efficient and rapid synthesis of new series of N -alkyl-2-aryl-5 H -imidazo[1, 2- b ]pyrazoles has been achieved in high yields through a three-component reaction of 3-amino-4-substituted pyrazoles, aromatic aldehydes and isocyanides mediated by acid catalysts. Abstract : An efficient and rapid synthesis of new series of N -alkyl-2-aryl-5 H -imidazo[1, 2- b ]pyrazoles has been achieved in high yields through a three-component reaction of 3-amino-4-substituted pyrazoles, aromatic aldehydes and isocyanides mediated by acid catalysts. In addition, a novel and straightforward approach to a sequential one-pot multicomponent reaction has been developed for the synthesis of hitherto undescribed 7, 7′-(substituted methylene)bis-imidazo[1, 2- b ]pyrazoles, starting from 3-amino-5-substituted (or unsubstituted) pyrazoles, various aldehydes and isocyanides. The reaction was performed under mild conditions in the presence of inexpensive zirconium(iv ) chloride as a catalyst. A library of 22 products was obtained in moderate to good yields.